Evolution of the brain developmental plan: Insights from agnathans - Murakami, Yasunori; Uchida, Katsuhisa; Rijli, Filippo M.; Kuratani, Shigeru (Developmental biology, 2005)
In vertebrate evolution, the brain exhibits both conserved and unique morphological features in each animal group. Thus, the molecular program of nervous system development is expected to have experienced various changes through evolution. In this review, we discuss recent data from the agnathan lamprey (jawless vertebrate) together with available information from amphioxus and speculate the sequence of changes during chordate evolution that have been brought into the brain developmental plan to yield the current variety of the gnathostome (jawed vertebrate) brains.